Culture of Critical Discourse on Education and Science - M. B. Sapunov; Kh. G. Tkhagapsoev (Moscow Polytechnic University, 2018)
The article addresses the problems concerning the formation of the methodology of critical analysis of Russian strategies, which are aimed at reforming and managing of education and science on the basis of modern social science and Humanities studies and the principles of the interdisciplinary approach. The authors state the change of the critique vector - the transition from value-loaded political statements to scientific analysis of the objective factors determining social pathologies in education system. The situation today is characterized by the attempts to find and formulate an objectivated language to describe social reality. In particular, the researchers actively use the methodological potential of such concepts as "converted form", "red tapes", "Goodhart's law", "Thomas theorem" that are implemented as conceptual tools to comprehend and describe the specificity of educational system. The general meaning of the forming analytical strategy applied to education and science is that all the management actions are subject to "corrective" influence of these principles and laws. Within the framework of this approach critique of education (and the process of its reforming) is indivisible from the constructive analysis of education as a whole system with its immanent dimensions. This approach orients researchers towards studying the "ontological" and "essential" problems of education.